Hippocampal subfield and amygdala volumes are associated with difficulties in emotion regulation of depressed patients with a history of childhood maltreatment - Gálber, Mónika; Nagy, Szilvia Anett; Orsi, Gergely; Perlaki, Gábor; Tényi, Tamás; Czéh, Boldizsár; Simon, Maria (Frontiers in Psychiatry, 2025)
BackgroundPrevious studies indicate that hippocampal (subfield) and amygdala volumes may correlate with specific cognitive functions, coping strategies and emotion regulation. Here, we investigated associations between emotional processing and volumes of hippocampal subfields and amygdala. We focused on depressed patients since emotional dysregulation and hippocampal volume shrinkage are characteristic of them. Our hypothesis was that in depressed individuals, maladaptive emotional behaviors will correlate with hippocampal and amygdala volume shrinkage.MethodsWe recruited depressed patients with a history of childhood maltreatment (n=21), depressed patients without maltreatment (n=18), and matched controls (n=21). Their brains were imaged with magnetic resonance imaging and area reconstruction was performed with the FreeSurfer software. History of maltreatment was assessed with Childhood Trauma Questionnaire (CTQ). Emotion processing difficulties were evaluated using the Cognitive Emotion Regulation Questionnaire (CERQ), Difficulties in Emotion Regulation Scale (DERS), Toronto Alexithymia Scale (TAS) and Reading the Mind in the Eyes Test (RMET).ResultsDepressed patients, especially maltreated subjects had small, but nonsignificant hippocampal and amygdala volume decrease (≤10%) and displayed pronounced difficulties in emotion regulation. In maltreated individuals, we found positive correlations between CERQ–rumination and volume of the right CA3, as well as between CERQ–positive-reappraisal and volume of the left presubiculum. In maltreated individuals, CTQ–emotional-abuse scores showed positive correlation with amygdala volumes of both hemispheres. In non-maltreated depressed patients, we found negative correlations between CERQ–rumination and volumes of the right hippocampus and amygdala, as well as several subfields of the right hippocampus. Furthermore, in non-maltreated depressed patients, CTQ–emotional-neglect had a positive correlation with the volume of the right CA3. Overall, among the tests, CERQ–rumination scores had the largest number of correlations with hippocampal subfield volumes mainly in non-maltreated depressed subjects. We found no correlation between alexithymia and brain area. Amygdala volumes had very few correlations, and only with CERQ and CTQ scores.LimitationsRelatively small sample size, cross-sectional design, retrospective self-report questionnaire to assess adverse childhood experiences and no amygdala subnuclei segmentation.ConclusionsWe could not confirm our hypothesis that maladaptive emotional behavior is associated with hippocampal volume shrinkage. Future studies should preferably focus on functional neuroimaging when examining complex emotional phenomena.